ISOTOPIC STUDY OF NEUTRON CAPTURE EFFECTS ON SM AND GD IN CHONDRITES - Hidaka H.; Ebihara M.; Yoneda S. (My University, 2000)
Isotopic compositions of Sm and Gd in eight chondrites (Mezo-Madaras, Parnallee, Otis, Suizhou, Zhaodong, Allende, Bruderheim and Y-74191) were measured to study neutron capture effects due to the interaction of cosmic rays with planetary materials in space. The anti-correlation of 149Sm/152Sm with 150Sm/152Sm and of 157Gd/160Gd with 158Gd/160Gd in the meteorites provides evidence for neutron capture effects in these chondrites. Isotopic deviations observed in the eight chondrites are ε149Sm=-0.35 to -1.93, ε150Sm=+0.87 to +4.35, ε157Gd=-2.82 to -1.21 and ε158Gd=+0.33 to +1.66, which correspond to thermal neutron fluences of (1.03-5.17)x1015 n cm-2. The combination of isotopic data from Sm-Gd in this study and Ne-Kr from the literature provides information on the secondary produced thermal (<0.1 eV), epi-thermal (30-300 eV) and fast (>5 MeV) neutron fluences for chondrites, and it is used here to estimate the neutron energy distribution for six L- and LL-chondrites. From the difference of distribution of thermal, epi-thermal and fast neutron fluences in individual chondrites, the depth of the samples inside the meteoroid is discussed. In Allende, the isotopic anomalies observed may be due not only to neutron capture reactions but also to additions of r-process nuclides of Sm and Gd.
Keywords: CHONDRITES; NEUTRONS; ISOTOPE RATIOS; SAMARIUM; GADOLINIUM